The adaptive reuse of obsolete shophouses in the core zone of Melaka, Malaysia as boutique hotels - Binti Ab Rashid, Nor Syahila (2020)
Rapid economic development and restructuring mean that there are more old and obsolete buildings in large cities. Many of these buildings represent different eras and building typologies. Some, such as the distinctive shophouses of Southeast Asia, are important heritage legacies. The desire to undertake research related to the adaptive reuse of shophouses arises from the abandonment and demolition of many of these unique urban assets. However, preserving shophouses for their original use might not necessarily be appropriate as the nature of uses can change over time. Therefore, adaptive reuse is suggested to extend the service of such buildings and to avoid obsolescence being used as a justification for demolition. The aim of this research is to find the best formulas for revitalising and converting obsolete shophouses in the Core Zone of Melaka, Malaysia for suitable uses. In this context, this research demonstrates a highly detailed understanding of the adaptive reuse process for the conversion of shophouses to hotel-type accommodation (boutique hotels), which is an important reuse function for these shophouses. This research incorporates qualitative research through fieldwork and the case study approach. An on-site survey, observations and interviews were conducted as the primary means of data collection to gather information from the researcher herself as the surveyor and observer as well as from interviewees associated with the conversion process. Content analysis was used as the primary means of analysis for the collected data, with the assistance of NVivo software, to enable the development of key themes. The research findings indicate that the majority of conservation projects in this area involve reuse, with cafés and restaurants being the most popular choice for partially reused shophouses, and hotels and motels for fully reused shophouses. Legal provisions, tourism demand, inscription demand, profitability, outdated original function, building vacancy and accessibility are considered contributing factors for these reuse activities. Functional and social obsolescence are identified as the key reasons these shophouses become obsolete. The results confirm earlier findings on the important role and beneficial impact of the adaptive reuse of shophouses. Nevertheless, there are major concerns regarding constructional, spatial, servicing and financial barriers. These elements should be considered when converting Malaysian shophouses for other functions, particularly for use as boutique hotels. Conversion into boutique hotels is highly regulated, and this research emphasises the possibility of disruption of the original character of the building, and potential loss of authenticity, when complying with the building codes. In addition, there is controversy as to the ideal approach to making shophouses in this area reach the minimum standards for a boutique hotel. The findings of this study have implications for theory development, practice and application, and future research. A better understanding of the adaptive reuse process could be the basis for improved policy and design interventions for obsolete shophouses in this area, keeping them in active use. Their survival is crucial to maintaining the continuous inscription of Melaka on the UNESCO World Heritage List.